PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS PUZZLE "SUGAM" UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS IV SEKOLAH DASAR - Sarah Saripah; Maha Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to: (1) determine the design of the "Sugam" puzzle-based learning media to improve the learning outcomes of fourth-grade elementary school students in IPAS (Integrated Science and Social Studies), (2) assess the feasibility of the media through validation by experts in content, media, and language, and (3) evaluate the effectiveness of the Sugam media. This research uses the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The instruments used are teacher response questionnaires (92%) and student response questionnaires (98%) to measure the practicality of the media. The expert validation results indicate the feasibility of the media, with percentages of 90% (media expert), 96% (language expert), and 98% (content expert). The field test results show a significant improvement in the pre-test (56) and post-test (94) scores, with an N-gain value of 0.86, indicating a high improvement. Thus, the developed learning media is effective for use in teaching.